Melatonin Prevents Mice Cortical Astrocytes From Hemin-Induced Toxicity Through Activating PKCα/Nrf2/HO-1 Signaling in vitro - Chen, Xiao; Xi, Zhiyu; Liang, Huaibin; Sun, Yuhao; Zhong, Zhihong; Wang, Baofeng; Bian, Liuguan; Sun, Qingfang (Frontiers in Neuroscience, 2019)
Secondary injury mediated by oxidative stress leads to deterioration of neurological function after intracerebral hemorrhage (ICH). Cortical astrocytes are one of the most important cells in the central nervous system (CNS). It is absolutely critical to maintain redox homeostasis by protecting oxidative stress. Hemin is a product of hemoglobin degradation, which has strong toxicity and can induce reactive oxygen species (ROS). Melatonin (Mel) and its metabolites are well tolerated without toxicity, prevent tissue damage as well as effectively assist in scavenging free radicals. We evaluated the hemin neurotoxicity to astrocytes and the resistance of Mel-treated astrocytes to hemin neurotoxicity. And we found Mel induced upregulation and nuclear translocation of Nrf2 in astrocytes, and upregulation of HO-1, which contributed to the reduction of ROS accumulation and cell apoptosis. Luzindole (Luz), the Mel inhibitor, suppressed HO-1 and Nrf2 expression upregulated by Mel and increased cell apoptosis rate. The upregulation of HO-1 induced by Mel was depressed by knocking down Nrf2 expression by siRNA, which also decreased the resistance of astrocytes to toxicity of hemin. Mel activates astrocytes through Nrf2/HO-1 signaling pathway to acquire resistance to toxicity of hemin and resist from oxidative stress and apoptosis. It is proposed that Mel and Nrf2 signaling pathways could become targets of neuroprotection after ICH.